What's on your hard drive?. - O'Hanlon, Charlene (ACM queue : architecting tomorrow's computing., 2005)
The tools on our hard drives vary widely in how directly they allow us to access the underlying hardware. Accordingly, many of our readers are most comfortable working as close to the machine as possible. Sometimes called "bare metal" programmers, they prefer the fewest possible layers of abstraction separating their code from the hardware. Others prefer tools that specialize in tasks less directly tied to the machine, creating models or even coding in Java with nary a thought of bits and bytes. Despite their fundamental differences, both types of tools inspire equal amounts of love and hate in their users, some of whom love tools for the same reasons (such as having a command line interface) that others hate them. We would like to hear more about which ones you love and hate, whatever your bias, at www.acmqueue.com